Disneyfikacja literatury young adult: powieściowe retellingi baśni z perspektywy postfeministycznej - Kostecka, Weronika (Zagadnienia Rodzajów Literackich, 2025)
This article examines the phenomenon of Disneyfication in young adult (YA) literature that offers retellings of fairy tales popular within the Western cultural canon. The author questions the actual novelty of these narratives, arguing that many of the analyzed texts, despite claims of feminist reinterpretation, remain thematically and structurally entrenched in familiar patriarchal patterns. The discussion draws on postfeminist discourse as manifested in Walt Disney Studios’ live-action adaptations of classic fairy tales — both literary (e.g., by Mme de Beaumont, Perrault, Andersen) and animated (produced earlier by Disney itself) — and identifies its key features. The article begins by clarifying the concepts of postfeminism and Disneyfication (as distinct from Disneyization) in the context of popular culture and YA. It then turns to YA fairy-tale retellings originally published in English after the year 2000, when the global YA market began to experience a marked influx of such texts. The selected novels are treated as part of Western popular culture and analyzed accordingly.